Scale-dependent microwave heating of comminuted meat: Roles of pore structure and component interactions - Wenjin Gong; Xing Chen; Yuan Tao; Sijia Wang; Jian Hu; Xidong Jiao; Bowen Yan; Nana Zhang; Wei Chen; Paulo Cezar Bastianello Campagnol; Daming Fan (Journal of Food Engineering, 2027)

Enhancing heating uniformity in microwave pasteurization through eccentric rotation and bubbling: method and applications - Kunyao Luo; Yuan Tao; Yuqiang Song; Jiayi Zhou; Bowen Yan; Huayu Yang; Xing Chen; Nana Zhang; Michael G. Gänzle; Wei Chen; Daming Fan (Food Research International, 2026)

κ-carrageenan mediated microwave 3D printing of Spirulina: Realizing immediate curing through temperature-dependent phase transition - Dingxuan Xu; Zilong Zhao; Hangwei Zhang; Xiaolin An; Nana Zhang; Bowen Yan; Yu Liu; Yang Zhang; Hongyuan Cheng; Daming Fan (Food Bioscience, 2026)

A data-driven intelligent framework for silver carp (Hypophthalmichthys molitrix) surimi gel properties prediction and quality improvement - Weijian Ye; Mingyi Hu; Xiaotong Cheng; Xidong Jiao; Huifang Yang; Shiwen Zhang; Xiude Wu; Bowen Yan; Tenghui Yu; Jianlian Huang; Jinlin Zhu; Daming Fan (Food Research International, 2026)

Unveiling the protective mechanism of rapid microwave heating on Lactoferrin: insights from structural integrity and bioactivity - Yaxin Huang; Yuan Tao; Huayu Yang; Bowen Yan; Nana Zhang; Xing Chen; Bo Hu; Hao Zhang; Wei Chen; Daming Fan (Food Research International, 2026)

Numerical modeling and experimental validation of uniform heating in a slot waveguide microwave system for continuous-flow high-viscosity liquids - Bowen Yan; Yuying Sun; Zhen Li; Haifeng Diao; Jianlian Huang; Heng Jiang; Xiaowei Yan; Nana Zhang; Huayu Yang; Huacheng Zhu; Wei Chen; Daming Fan (Chemical Engineering Journal, 2026)

A stage-controlled combined heating strategy for microwave-assisted air frying: A case study of frozen pre-fried French fries - Shichao Wang; Huayu Yang; Yuan Tao; Xiangwei Tang; Bowen Yan; Daming Fan (Innovative Food Science & Emerging Technologies, 2026)

Embodied artificial intelligence in the food supply chain: Innovations, challenges, and future perspectives - Chongyu Wang; Chenglong Lv; Yixin Gao; Yiyang He; Xiyao Zhang; Zhikun Zhang; Weiqing Min; Dachuan Zhang; Daming Fan; Weihao Wang; Peihua Ma; Fengzhong Wang (Trends in Food Science & Technology, 2026)

Harnessing mycelium-based morphology of filamentous fungi in food biomanufacturing: Integrated advances, challenges, and future perspectives - Mengmeng Xu; Song Ming; Jiahao Cui; Yuxi Guo; Liting Zhao; Lei Chen; Guiyang Shi; Daming Fan; Zhongyang Ding (Trends in Food Science & Technology, 2026)

Dynamic speed adjustment based on time-code enhances filament consistency in continuous switching 3D food printing - Zilong Zhao; Xiaolin An; Nana Zhang; Dingxuan Xu; Bo Hu; Xing Chen; Bowen Yan; Yu Liu; Wei Chen; Daming Fan (Journal of Food Engineering, 2026)

Directional freezing exploits meat anisotropy to preserve muscle fibers microstructural integrity and mitigate freezing loss - Jian Hu; Xing Chen; Wenjin Gong; Hao Zou; Bo Hu; Nana Zhang; Bowen Yan; Wei Chen; Daming Fan (Journal of Food Engineering, 2026)

Mechanisms of structural deterioration in red tilapia fillets during freeze-thaw cycles: Ice crystal dynamics-driven muscle microstructural damage - Hao Zou; Yifan Tao; Xidong Jiao; Yun Ma; Huifang Yang; Chengyu Qian; Jian Hu; Pengbo Bian; Jianlian Huang; Fujiang Cai; Jun Qiang; Pao Xu; et al. (Food Research International, 2026)

κ-Carrageenan facilitates the instant curing of chlorella powders during microwave 3D printing - Xiaolin An; Zilong Zhao; Zixian Zhu; Dan Huang; Xing Chen; Bowen Yan; Jianlian Huang; Nana Zhang; Daming Fan (Food Hydrocolloids, 2026)

Innovative strategies for gel-type meat products: Advancing healthy reformulation and sustainable processing - Sijia Wang; Xing Chen; Bowen Yan; Xidong Jiao; Nana Zhang; Daming Fan (Trends in Food Science & Technology, 2026)

Smartphone-based microfluidic colorimetric sensor for on-site multiplex soil nutrient analysis - Fan Luo; Ning Liu; Fengjing Cao; Yachao Liu; Renxiang Jiang; Daming Dong (Computers and Electronics in Agriculture, 2026)

Microwave vacuum evaporation of sugar solutions: Analysis of dielectric and microwave absorption properties - Yuan Tao; Bowen Yan; Nana Zhang; Jianxin Zhao; Wei Chen; Daming Fan (Journal of Food Engineering, 2026)

Mesoscopic properties of Antarctic krill protein amyloid fibrils described by soft matter physics - Yifan Zhang; Xing Chen; Hang Qi; Xidong Jiao; Nana Zhang; Bowen Yan; Daming Fan (Food Structure, 2026)

Corrigendum to “Processing suitability of three tilapia species as alternative freshwater surimi: A comprehensive evaluation from muscle physicochemical to gelling properties” [Food Chem. 492 (2025) 145540] - Hao Zou; Xidong Jiao; Yifan Tao; Sirui Zeng; Jun Qiang; Jian Hu; Bowen Yan; Wei Chen; Pao Xu; Daming Fan (Food Chemistry, 2025)

Recent advances in microwave inactivation of foodborne pathogens: Key factors, mechanisms, and future perspectives - Kunyao Luo; Yuan Tao; Huayu Yang; Bowen Yan; Hao Zhang; Wei Chen; Daming Fan (Trends in Food Science & Technology, 2025)

Exploring the potential of microwave processing for improved microbial safety and nutritional quality of liquid milk - Yaxin Huang; Yuan Tao; Huayu Yang; Jian Zhang; Bowen Yan; Hao Zhang; Wei Chen; Daming Fan (Food Research International, 2025)

Comparative study on the degradation mechanism of C-phycocyanin under different heat treatments: Insights from spectroscopy and molecular dynamics simulations - Jian Zhang; Yuan Tao; Chaoyi Xue; Bowen Yan; Xing Chen; Nana Zhang; Hao Zhang; Wei Chen; Daming Fan (Food Chemistry, 2025)

Processing suitability of three tilapia species as alternative freshwater surimi: A comprehensive evaluation from muscle physicochemical to gelling properties - Hao Zou; Xidong Jiao; Yifan Tao; Sirui Zeng; Jun Qiang; Jian Hu; Bowen Yan; Wei Chen; Pao Xu; Daming Fan (Food Chemistry, 2025)

Domain knowledge, just evaluation, and robust data standards are required to advance AI in food science - Dachuan Zhang; Meihui Liu; Zhaoshuo Yu; Hanlin Xu; Stephan Pfister; Giulia Menichetti; Xingran Kou; Jinlin Zhu; Daming Fan; Pingfan Rao (Trends in Food Science & Technology, 2025)

Metabolites profile and endogenous enzymes changes in pre-dehydrated surimi: Mechanistic insights into gelling properties and flavor characteristics - Sirui Zeng; Xidong Jiao; Yongwei Niu; Xiaowei Yan; Nana Zhang; Hao Zhang; Bowen Yan; Daming Fan (Food Research International, 2025)

Muscle quality enhancement of largemouth bass (Micropterus salmoides) by alkaline water cultured environment: A comprehensive evaluation of physical features, nutrient composition, and flavor characteristics - Jixiang Hua; Yifan Tao; Xidong Jiao; Daming Fan; Siqi Lu; Yalun Dong; Wen Wang; Bingwen Xi; Jun Qiang (Food Chemistry, 2025)

Artificial intelligence in smart seafood safety across the supply chains: Recent advances and future prospects - Xidong Jiao; Jinlin Zhu; Weijian Ye; Hao Zou; Bowen Yan; Nana Zhang; Jun Qiang; Yifan Tao; Hao Zhang; Dachuan Zhang; Daming Fan (Trends in Food Science & Technology, 2025)

Formation of Ce(IV)-borate intrinsic colloid alters Ce(IV) transport: The role of Ce(IV) concentration, pH, ionic strength and humic acid - Kang Chen; Guangjie Gao; Fayang Wu; Ye Fan; Xin Zhao; Ganlin Zu; Qichen Yao; Daming Zhang; Qiang Jin; Zhijun Guo; Zongyuan Chen (Journal of Hazardous Materials, 2025)

Current physical processing technologies for salt reduction in prepared dishes - Jian Hu; Yuan Tao; Xidong Jiao; Xing Chen; Nana Zhang; Bowen Yan; Xiangwei Tang; Jianlian Huang; Wei Chen; Daming Fan (Food Research International, 2025)

Insight into the impact of pre-cooking and freezing on the colour stability of pakchoi during thermal processing: A study on chlorophyll and organic acid changes - Wenjin Gong; Xingwei Li; Jian Hu; Wulian Hu; Nana Zhang; Xing Chen; Bowen Yan; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Food Chemistry, 2025)

Microwave irradiation benefits fructan degradation in sourdough steamed cake by tunning the β-fructosidase FosE-substrate interaction - Xiaoyue Ying; Yuan Tao; Yuan Yuan; Dawei Ni; Wenli Zhang; Bowen Yan; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Food Chemistry, 2025)

Milk vetch (Astragalus sinicus L.) affects microbial-driven rice straw decomposition in multiple stages - Xinling Ma; Qingjun Dai; Wenjing Qin; Jia Liu; Xiaoli Liu; Ling Chen; Jianbo Fan; Meng Wu; Daming Li; Ming Liu (Plant and Soil, 2025)

Dielectric behavior of frozen dough during thawing: Insights into phase transition, mobility, and migration of water - Yiling Yang; Yuan Tao; Yejun Wu; Bowen Yan; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Journal of Food Engineering, 2025)

Harnessing pea proteins for thermo-reversible gels: Novel strategy and molecular principle - Yanna Zhang; Xing Chen; Xingwei Li; Yuan Tao; Nana Zhang; Bowen Yan; Hao Zhang; Daming Fan (Food Research International, 2025)

A novel method for high-temperature microwave 3D printing of golden thread surimi: Combination of thermally reversible gelatin and κ-carrageenan - Yin Xiong; Zilong Zhao; Nana Zhang; Zixian Zhu; Yu Liu; Hao Zhang; Wei Chen; Daming Fan (Food Hydrocolloids, 2025)

Effect and mechanisms of mechanical pre-dehydration treatment on gelling and physicochemical properties of unwashed silver carp (Hypophthalmichthys molitrix) surimi - Sirui Zeng; Xidong Jiao; Xiaowei Yan; Bowen Yan; Tenghui Yu; Yongwei Niu; Heng Jiang; Nana Zhang; Hao Zhang; Wei Chen; Daming Fan (Food Chemistry, 2025)

Food recommendation towards personalized wellbeing - Guanhua Qiao; Dachuan Zhang; Nana Zhang; Xiaotao Shen; Xidong Jiao; Wenwei Lu; Daming Fan; Jianxin Zhao; Hao Zhang; Wei Chen; Jinlin Zhu (Trends in Food Science & Technology, 2025)

Synthesis of value-added uridine 5'-diphosphate-glucose from sucrose applying an engineered sucrose synthase counteracts the activity-stability trade-off - Liting Zhao; Zhongbao Ma; Linpei Zhang; Yu Shen; Lei Chen; Youran Li; Sha Xu; Guiyang Shi; Daming Fan; Zhongyang Ding (Food Chemistry, 2025)

Feasibility of continuous switching 3D printing on surimi - Zilong Zhao; Erwei Shang; Nana Zhang; Yin Xiong; Yu Liu; Hao Zhang; Wei Chen; Daming Fan (Journal of Food Engineering, 2025)

Spirulina platensis components mitigate bone density loss induced by simulated microgravity: A mechanistic insight - Jian Zhang; Yaxin Huang; Ning Bai; Yuying Sun; Ke Li; Huan Ruan; Bowen Yan; Jian Hu; Nana Zhang; Hao Zhang; Wei Chen; Daming Fan (Food Chemistry, 2025)

Precooked state based on protein denaturation kinetics impacts moisture status, protein oxidation and texture of prepared chicken breast - Bowen Wang; Xing Chen; Bowen Yan; Nana Zhang; Yuan Tao; Jian Hu; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Food Chemistry, 2025)

Improvement of heat treated spirulina proteins and their enzymatic hydrolysates on osteoporosis under simulated microgravity - Jian Zhang; Yuying Sun; Yaxin Huang; Huan Ruan; Bowen Yan; Nana Zhang; Hao Zhang; Wei Chen; Daming Fan (Food Bioscience, 2024)

Dimensional reduction of meat structure to create novel applications - Nana Zhang; Xing Chen; Xidong Jiao; Bowen Yan; Daming Fan (Current Opinion in Food Science, 2024)

Potential in microwave combined with hot air for home cooking - Bowen Yan; Yuying Sun; Xiangwei Tang; Daming Fan (Current Opinion in Food Science, 2024)

Elemental and particle size fractionation during the transport of Eu(III)-silicate colloids in water-saturated porous media - Daming Zhang; Xin Zhao; Ganlin Zu; Kang Chen; Guangjie Gao; Ye Fan; Qiang Jin; Zongyuan Chen; Zhijun Guo (Journal of Hazardous Materials, 2024)

Microwave-induced thermal response and protein variation of oil-water biphasic systems in foods: A Case study of anhydrous butter and skim milk - Yuqing Tao; Yuan Tao; Huayu Yang; Bowen Yan; Nana Zhang; Yan Zhang; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Journal of Food Engineering, 2024)

Solubilization of fish myofibrillar proteins in NaCl and KCl solutions: A DIA-based proteomics analysis - Xidong Jiao; Xingying Li; Nana Zhang; Bowen Yan; Jianlian Huang; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Food Chemistry, 2024)

Unraveling the binding mechanisms of transglutaminase and substrate subjected to microwaves: Molecular docking and molecular dynamic simulations - Yuan Tao; Jiawei Xu; Nana Zhang; Xidong Jiao; Bowen Yan; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Food Chemistry, 2024)

Microwave heat-induced aggregation behavior of fish myofibrillar protein: New insights from nano- and micro-structural observation - Xidong Jiao; Xingying Li; Nana Zhang; Bowen Yan; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Food Hydrocolloids, 2024)

Numerical solution-based algorithm assisted development of a continuous flow microwave reactor - Huayu Yang; Zhanglu Yan; Huacheng Zhu; Bowen Yan; Wei Chen; Daming Fan (Chemical Engineering Journal, 2024)

Beef tenderization without exacerbating the cooking loss: The way of enzymatic deamidation - Yue Wang; Xing Chen; Peng Zhou; Daming Fan (Food Bioscience, 2024)

Effects of distinct lipid phases and packaging on alleviating the quality deterioration of surimi gels during frozen storage - Yuxin Wang; Xidong Jiao; Nana Zhang; Bowen Yan; Haochen Ding; Weijian Ye; Jianlian Huang; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Food Bioscience, 2024)

Measurement of perfluoroalkyl substances in drinking water sources by DGT sampler with a novel fluorinated graphite binding gel - Fan Dong; Fan Ge; Xinting Zhao; Daming Sun; Suyu Ren; Yan Wang; Feng Tan (Science of The Total Environment, 2024)

Land cover change and its response to water level around Tonle Sap Lake in 1988–2020 - Jing Zhang; Kai Ma; Hui Fan; Daming He (Journal of Geographical Sciences, 2024)

Green and sustainable microwave processing of surimi seafood: A review of protein component interactions, mechanisms, and industrial applications - Xidong Jiao; Huayu Yang; Xingying Li; Hongwei Cao; Nana Zhang; Bowen Yan; Bo Hu; Jianlian Huang; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Trends in Food Science & Technology, 2024)

Dielectric and microwave-absorbing behavior of hydrated wheat starch-gluten systems in relation to water mobility - Yejun Wu; Bowen Yan; Yuan Tao; Nana Zhang; Yin Zhang; Hao Zhang; Wei Chen; Jianxin Zhao; Daming Fan (Journal of Food Engineering, 2024)

Continuous flow microwave processing of liquid whole egg: Pasteurization and functional characteristics evaluation - Huayu Yang; Mengqi Sun; Bowen Yan; Nana Zhang; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Innovative Food Science & Emerging Technologies, 2023)

Conformation and hydration property of low-acetyl gellan gum under microwave irradiation: Experiments and molecular dynamics simulations - Bowen Yan; Tiantian Chen; Yuan Tao; Nana Zhang; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Food Hydrocolloids, 2023)

Computational study on radio frequency thawing of irregularly shaped aquatic product: Using hairtail fish as an example - Hanting Jiang; Huayu Yang; Wenhai Zhang; Bowen Yan; Nana Zhang; Jianlian Huang; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Journal of Food Engineering, 2023)

Physicochemical changes and comparative proteomics analysis of hairtail (Trichiurus lepturus) fish muscles during frozen storage - Bowen Yan; Wenlu Bai; Yuan Tao; Weijian Ye; Wenhai Zhang; Nana Zhang; Jianlian Huang; Wei Chen; Daming Fan (Food Bioscience, 2023)

Decoupling thermal effects and possible non-thermal effects of microwaves in vacuum evaporation of glucose solutions - Yuan Tao; Bowen Yan; Nana Zhang; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Journal of Food Engineering, 2023)

Effects of quercetin on emissions of aldehydes from heated docosahexaenoic acid (DHA)-fortified soybean oil - Zhenyu Fan; Li Wang; Qingqing Jiang; Daming Fan; Jianbo Xiao; Mingfu Wang; Yueliang Zhao (Journal of Hazardous Materials, 2023)

Integrating precipitation zoning with random forest regression for the spatial downscaling of satellite‐based precipitation: A case study of the Lancang–Mekong River basin - Jing Zhang; Hui Fan; Daming He; Jiwei Chen (International Journal of Climatology, 2019)
Downscaling satellite‐based precipitation to fine scales is crucial for deepening our understanding of global hydrologic cycles and water‐related issues. In this study, a novel approach that integrates precipitation zoning with random forest regression is proposed for the spatial downscaling of satellite‐based precipitation. Precipitation zoning is delineated through iterative rotated empirical orthogonal function (REOF) analyses of ground‐ and satellite‐based precipitation observations. Random forest regression is applied to link the satellite‐based precipitation to 1‐km‐resolution predictors such as latitude (Lat), longitude (Lon), elevation, aspect, slope, and the normalized difference vegetation index (NDVI). The accuracy of the resultant downscaled precipitation is evaluated based on five statistical evaluation indices. The performance of the proposed approach is exemplified in the Lancang–Mekong River basin, taking Tropical Rainfall Measuring Mission (TRMM) 3B43 and Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks–Climate Data Record (PERSIANN–CDR) products acquired in 2001 (wet year), 2005 (normal year), and 2009 (dry year) as the databases. The results show that seven precipitation subregions can be roughly distinguished in the study basin. Zoning‐based downscaling outperforms non‐zoning‐based downscaling in terms of accuracy, resulting in statistically significant reductions in root mean square error (RMSE) and mean absolute error (MAE) of 1–17% across the entire basin. Among the selected predictors, the variables Lat and Lon are the most important for precipitation estimation, whereas the remaining variables have lesser and subregion‐dependent importance. The proposed approach is promising for generating high‐spatial‐resolution precipitation data in regions with sparse ground‐based observations and differentiated climatic regimes.

Fish Assemblage Responses to a Low-head Dam Removal in the Lancang River - Chengzhi Ding; Xiaoming Jiang; Lieen Wang; Hui Fan; Liqiang Chen; Jinming Hu; Hailong Wang; Yifeng Chen; Xiaotao Shi; Hao Chen; Bohui Pan; Liuyong Ding; et al. (Chinese Geographical Science, 2019)

Trends in precipitation over the low latitude highlands of Yunnan, China - Hui Fan; Jinming Hu; Daming He (Journal of Geographical Sciences, 2013)